Profitabilitas, Leverage dan Pengungkapan Corporate Social Responsibility dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Dewi, Made Ayu Bintang Cyntia; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 31 No 11 (2021)DO - 10.24843/EJA.2021.v31.i11.p11, 2021)
This study aims to obtain empirical evidence of the effect of profitability, leverage on CSR disclosure with firm size as moderating. This study focuses on mining companies, where mining companies have the greatest impact on environmental damage around the company's environmental area. The sample obtained was 33 companies using purposive sampling technique. The data analysis technique used was moderated regression analysis (MRA). The results show that profitability has a positive effect on CSR disclosure, leverage has a positive effect on CSR disclosure, firm size strengthens the effect of profitability on CSR disclosure and firm size is not able to strengthen the influence of leverage on CSR disclosure. Keywords : CSR Disclosure; Profitability; Leverage; Company Size.